2012
DOI: 10.1103/physrevb.86.174108
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic atomic vibrations in the relaxor ferroelectric Pb(Mg1/3Nb2/3)O

Abstract: Structural analyses of the relaxor ferroelectric material Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) with single-crystal x-ray diffraction under pressure in a diamond anvil cell indicate static atomic displacement and chemical disorder. Difference Fourier analysis within the framework of a harmonic oscillator model for the atomic vibrations reveals residual electron density on both the Pb and Nb (Mg) sites. Pb atoms in the A site of the ABO 3 perovskite structure exhibit a greater displacement than the Nb(Mg) atoms in the B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It has been shown that the butterfly shaped diffuse X-ray scattering is originated from PNRs in relaxors and is gradually suppressed with increasing pressure. 21,22,24,37,49 The Raman spectra obtained at high pressure in Pb-based relaxors is inconsistent with paraelectric cubic symmetry, and it also differs from the Raman spectra observed at low temperatures and ambient pressures. Several high-pressure studies on Pb-based relaxors such as PSN, 20 PMN, 22 (5) suggested that the transition to the high-pressure phase involves octahedral tilting.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been shown that the butterfly shaped diffuse X-ray scattering is originated from PNRs in relaxors and is gradually suppressed with increasing pressure. 21,22,24,37,49 The Raman spectra obtained at high pressure in Pb-based relaxors is inconsistent with paraelectric cubic symmetry, and it also differs from the Raman spectra observed at low temperatures and ambient pressures. Several high-pressure studies on Pb-based relaxors such as PSN, 20 PMN, 22 (5) suggested that the transition to the high-pressure phase involves octahedral tilting.…”
Section: Discussionmentioning
confidence: 72%
“…Recent theoretical calculations and experiments point out that the displacement of Pb cation in these materials have strong correlations along particular crystallographic directions, that gives diffuse scattering in relaxor materials. 37,49 A common feature of high-pressure phase of Pb-based relaxors is a new peak appearing around 380 cm À1 in Raman spectra for all these studied Pb-based relaxor samples including PbTiO 3 . A similar peak appeared in PIN above 1 GPa, and the frequency of this peak is located around the bending mode region in general.…”
Section: Discussionmentioning
confidence: 99%
“…This is why no further structural analysis is done on the sole basis of Bragg reflections. Notably, an accurate study of strong Bragg reflections for an analysis of anharmonic thermal vibrations does not report any superstructure spots up to 73 kbar [15]. That could be due to a point detector technique and collection of the data only for Bragg nodes expected for Pm3m symmetry, which obviously makes the results over-interpreted.…”
Section: Discussionmentioning
confidence: 96%
“…We adopted a multimodal distribution in the probability density function using cumulant expansion and Gram-Charlier series expansion [34] [35]. We take into account of fourth-rank in T ij (hkl) in eq.…”
Section: Anharmonic Thermal Parametermentioning
confidence: 99%